To analyze the translation of the function \( f(x) = \sqrt{x} \) to \( g(x) \), we can look at the transformations involved based on the expressions given.
-
For \( g(x) = \sqrt{x + 2} \):
- We can set the transformation expression \( x + 2 \) to zero and solve for \( x \): \[ x + 2 = 0 \implies x = -2 \]
- This result indicates a horizontal shift to the left by 2 units. Therefore, the transformation from \( f(x) = \sqrt{x} \) to \( g(x) = \sqrt{x + 2} \) represents a translation of the original function 2 units to the left.
-
For \( g(x) = \sqrt{x - 2} \):
- Similarly, we can set the transformation expression \( x - 2 \) to zero and solve for \( x \): \[ x - 2 = 0 \implies x = 2 \]
- This result indicates a horizontal shift to the right by 2 units. Therefore, the transformation from \( f(x) = \sqrt{x} \) to \( g(x) = \sqrt{x - 2} \) represents a translation of the original function 2 units to the right.
In summary:
- For \( g(x) = \sqrt{x + 2} \), it's a horizontal shift left by 2 units.
- For \( g(x) = \sqrt{x - 2} \), it's a horizontal shift right by 2 units.